PENGARUH CITRA PERGURUAN TINGGI TERHADAP KEPUTUSAN KULIAH MAHASISWA - Ivan Fanani Qomusuddin; Siti Romlah (STAI Sebelas April Sumedang, 2021)
This study aims to determine how much influence the image of the university has on student college decisions at the Islamic Religious Education Study Program STIT At-Taqwa Ciparay Bandung. This research is field research with a quantitative approach. The data analysis technique used is a simple regression analysis technique through the help of the IBM SPSS version. 20 for windows. The population of this study was students of the Islamic Religious Education Study Program (PAI) STIT At-Taqwa Ciparay Bandung, totaling 497 students, and 123 students were taken as samples with random sampling technique. Data collection techniques were carried out by means of: observation, interviews, documentation, and closed questionnaires through google form media. Testing of research instruments and data was carried out through validity and reliability tests, linearity tests, and normality tests. The results showed that there was a significant and positive influence on the image of universities on student college decisions at the Islamic Religious Education Study Program (PAI) STIT At-Taqwa Ciparay Bandung by 53.4%, and the remaining 46.6% were influenced by other factors that were not researched. This shows that the better the image of STIT At-Taqwa Ciparay Bandung, the student's decision to study at the Islamic Religious Education Study Program (PAI) STIT At-Taqwa Ciparay Bandung will also be higher, for that the management of STIT At-Taqwa Ciparay Bandung should conduct better socialization and promotion to the community so that STIT At-Taqwa Ciparay Bandung is increasingly known by the public or prospective students.